Comparative Techniques of Medial Rectus Muscle Retraction for Endoscopic Exposure of the Medial Intraconal Space. Issue 3 (May 2016) - Lin, Giant C.; Freitag, Suzanne K.; Kocharyan, Armine; Yoon, Michael K.; Lefebvre, Daniel R.; Bleier, Benjamin S.
Objective: The medial rectus muscle (MRM) is the medial boundary to the intraconal space of the orbit, and retraction of the MRM is oftentimes necessary for endoscopic removal of intraconal tumors, e.g., orbital hemangioma. We evaluated each of the reported methods of MRM retraction for endoscopic orbital surgery and quantified the degree of intraconal exposure conferred by each method. Methods: Eight orbits from four cadaver heads were dissected. In each orbit, medial orbital decompression was performed and the MRM was retracted by using four previously described techniques: (1) external MRM retraction at the globe insertion point by using vessel loop (external group), (2) transseptal MRM retraction by using vessel loop (transseptal group), (3) transchoanal retraction of the MRM by using vessel loop (choanal group), and (4) transseptal four-handed technique by using double ball retraction by a second surgeon (transseptal double ball group). The length, height, and area of exposure of the medial intraconal space were quantified and compared. Results: The average ± standard deviation (SD) anterior-posterior exposures for the external group, transseptal group, and transseptal double ball group were 17.51 ± 3.39 mm, 16.59 ± 4.16 mm, and 18.0 ± 15.25 mm, respectively. The choanal group provided significantly less exposure (12.39 ± 3.44 mm, p = 0.049) than the other groups. The average ± SD vertical exposures for the transseptal group, choanal group, and transseptal double ball group were 12.53 ± 4.38 mm, 13.05 ± 5.86 mm, and 13.57 ± 3.74 mm, respectively. The external group provided significantly less exposure (4.51 ± 1.56 mm, p = 0.0072) than the other groups. The transseptal and transseptal double ball groups provided the greatest total access by surface area (58.88 ± 26.96 mm 2 and 62.94 ± 34.74 mm 2, respectively) compared with the external and choanal groups (34.82 ± 23.37 mm 2 and 43.10 ± 23.68 mm 2, respectively). Although the transseptal trajectory of MRM retraction was optimal, the difference in total area of exposure between the static vessel loop retraction and the dynamic, four-handed technique with double ball instrument retraction was not significant. Of note, the exposure provided by the choanal technique required the surgeon to work both above and below the muscle. Conclusion: Retraction of the MRM toward the choanae provided the least length of exposure, and external retraction exposed the least height and total area. Transseptal MRM retraction was most favorable and provided the largest endoscopic corridor to the medial intraconal space. A four-handed approach for endoscopic intraconal surgery of the orbit may offer advantages in dynamic adjustments in retraction.